Down syndrome: Cognitive and behavioral functioning across the lifespan. (18th May 2015) - Grieco, Julie; Pulsifer, Margaret; Seligsohn, Karen; Skotko, Brian; Schwartz, Alison
<x xml:space="preserve">Abstract</x> Individuals with Down syndrome (DS) commonly possess unique neurocognitive and neurobehavioral profiles that emerge within specific developmental periods. These profiles are distinct relative to others with similar intellectual disability (ID) and reflect underlying neuroanatomic findings, providing support for a distinctive phenotypic profile. This review updates what is known about the cognitive and behavioral phenotypes associated with DS across the lifespan. In early childhood, mild deviations from neurotypically developing trajectories emerge. By school‐age, delays become pronounced. Nonverbal skills remain on trajectory for mental age, whereas verbal deficits emerge and persist. Nonverbal learning and memory are strengths relative to verbal skills. Expressive language is delayed relative to comprehension. Aspects of language skills continue to develop throughout adolescence, although language skills remain compromised in adulthood. Deficits in attention/executive functions are present in childhood and become more pronounced with age. Characteristic features associated with DS (cheerful, social nature) are personality assets. Children are at a lower risk for psychopathology compared to other children with ID; families report lower levels of stress and a more positive outlook. In youth, externalizing behaviors may be problematic, whereas a shift toward internalizing behaviors emerges with maturity. Changes in emotional/behavioral functioning in adulthood are typically associated with neurodegeneration and individuals with DS are higher risk for dementia of the Alzheimer's type. Individuals with DS possess many unique strengths and weaknesses that should be appreciated as they develop across the lifespan. Awareness of this profile by professionals and caregivers can promote early detection and support cognitive and behavioral development. © 2015 Wiley Periodicals, Inc.